THE ROLE OF THE VILLAGE HEADMAN AS A DEVELOPMENT INFORMATION DISMINATION FOR THE COMMUNITY IN CIAKAR VILLAGE, SUB-DISTRICT OF CIPAKU, DISTRICT OF CIAMIS - Utep Muhammad Mu'ti; Eet Saeful Hidayat; Imam Maulana Yusuf (Faculty of Social And Political Science Universitas Galuh, 2021)
The purpose of this study is to determine the role of the Village Headman as the dissemination of development information for the community in Ciakar Village, Sub-district of Cipaku, District of Ciamis and to find out the obstacles and efforts that faced by the Village Headman as the dissemination of development information for the community in Ciakar Village, Sub-district of Cipaku, District of Ciamis. The research design used is descriptive analysis and a qualitative approach. The data used in this study are qualitative data consisting of primary data and secondary data. Data collection techniques in this study are using literature study and field studies in the form of observations and interviews, informants in this study were 13 (thirteen) people. Implementation of information dissemination for community development in the village of Ciakar has not run optimally. Based on field observations and interviews, there were still problems related to the implementation of information dissemination. From the research results, it can be seen that the role of the Village Headman as the Dissemination of Development Information for the Community in Ciakar Village, Sub-district of Cipaku, District of Ciamis is carried out based on three components which are actors, activity, and place. Based on the results of the study, the authors suggest to the village head to improve information management by involving parties who are competent in information technology so that the content or content of the resulting information is more attractive so that people do not act apathetic to information.